Discriminatory barriers for professional practice in Peruvian nurses - Quispe-Ilanzo, Melisa Pamela (2020)
Introduction: In Peru, the number of nurses has increased fourfold, and is the biggest professional group in the health sector; however, there would be factors that contribute with wage discrimination in the labor market. Objective: identify factors for labor discrimination in Peruvian nurses. Material and methods: A secondary analysis of the "National Survey of University Graduates and Universities 2014" was conducted. Probabilistic, stratified, single-stage and independent sample in each selected university included 548 nurses. Multivariate analysis was performed using logistic regression and the adjusted odds ratio (aOR) was obtained with its 95% confidence interval (95% CI) and Hosmer-Lemeshow goodness of fit test. Results: Women had a higher risk of unemployment (aOR: 3,401; 95%CI: 2.447-4.725) and total compensation of less than S/.1000 (aOR: 1.496; 95%CI: 1.229-1.821). Graduates of universities not located in Lima and Callao had a higher risk of: unemployment (aOR: 1.269; 95%CI: 1.105-1.457); work not related to vocational training (aOR: 2.603; 95%CI: 1.703-2.499); and total remuneration less than S/.1000 (aOR: 1.660; 95%CI: 1.456-1.892). If the main work was not related to vocational training exposes the professional to a higher risk of less than S/.1000 total remuneration (aOR: 11.125; 95%CI: 9.221-13.421) and it was decisive for having two or more occupations (aOR: 1,381; IC95 %: 1,196-1,594). The Hosmer-Lemeshow test showed that these factors provided better fit to the data (p> 0.05). Conclusion: Sex, etnicity, type of management and location of the university determine discrimination in Peruvian nurses for accessing to the labor market and their remuneration.